The Contribution of Da'wah For the Elderly in the Qur'an and Al-Hadith and its Implementation in the People of Bekasi City - Mohammad Shodiq Ahmad (Jurnal Syntax Transformation, 2023)
Elderly is the final stage in the journey of human life, where humans in general experience a lot of decline, weakening and reduced potential abilities and activities. So that the elderly appear weak, lethargic, sluggish, and tired. Their lives tend to be unemployed, inattentive, more rested, and not much activity. They can no longer be aggressive, agile and agile like they were when they were young. On the other hand, there is a general view (public opinion) circulating in the community, that the existence of the elderly (elderly) or often referred to as elderly (elderly human) still does not receive a positive response and is underestimated. Including the participation and contribution of the elderly in preaching and fighting in upholding the religion of Allah SWT. In fact, these da'wah activities must continue, continue, and continue to move from childhood, to old age. Because Islam is a missionary religion. A religion that must be driven by its carriers and callers. So Islam always encourages its people to always play an active role in carrying out these da'wah activities. Because da'wah is one of the important means of spreading Islamic teachings to the community. And in order to realize the Islamic religion which continues to exist throughout the ages, missionary workers (including the elderly) are needed who are constantly moving and rotating; continuous, ongoing, and continuous. Therefore, the study of the elderly and their contribution to da'wah is very important to do. This study aims to: First, explain who is the elderly, and the characteristics and characteristics attached to them; Second: explaining the verses of the Al-Qur'an and Al-Hadith which explain matters concerning humans who are in the elderly stage; Third, exploring the potential of the elderly in contributing (contribution) in da'wah; and Fourth, determining how the elderly are able to implement their preaching potential to the people of Bekasi City. This research method consists of: a. This type of research is descriptive qualitative, through library research and field research as well. Where in the library research it examines more on the concept of the verses of the Koran al-hadith on the elderly; b. While the technique of collecting data for field research, by means of interviews, observation and documentation, to get the results of real implementation studies (practices and applications) in the field. Furthermore, the collected data is processed and analyzed, so that it will get a more comprehensive research. The results of this study indicate that: First, the elderly are actually an important element in society that must be properly responded to for their potential in the da'wah movement; Second, there are potentials that are quite calculated in contributing their da'wah to the community. Third, there are areas of da'wah that can be moved by the elderly in implementing their da'wah contribution to the people of Bekasi City.